-33=-3n-4n

Simple and best practice solution for -33=-3n-4n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33=-3n-4n equation:


Simplifying
-33 = -3n + -4n

Combine like terms: -3n + -4n = -7n
-33 = -7n

Solving
-33 = -7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7n' to each side of the equation.
-33 + 7n = -7n + 7n

Combine like terms: -7n + 7n = 0
-33 + 7n = 0

Add '33' to each side of the equation.
-33 + 33 + 7n = 0 + 33

Combine like terms: -33 + 33 = 0
0 + 7n = 0 + 33
7n = 0 + 33

Combine like terms: 0 + 33 = 33
7n = 33

Divide each side by '7'.
n = 4.714285714

Simplifying
n = 4.714285714

See similar equations:

| 2/3x+1/4=5/6 | | 87=2x-5 | | 10x*y-50000=0 | | 13-2t=4 | | 28000=20000+0.3x | | Y=20000+0.3x | | 8=4p+12 | | 6x^2-3=4x | | 6x^2-3=3x | | 2-3(x-1)=-2-2(1-3x) | | 3(2x-5)=33 | | 1-(3-8x)=2(2x+4) | | a+68=-72 | | 4-8x+2x=6+5(x+4) | | 2y^3-18y+3y^2-27=0 | | x/8=17 | | 5.51+4.3a=67 | | 8+4x=2x+2+24 | | 68-f=-72 | | 0.074d-3.4=0.707 | | 12x+12=36+6x | | f-68=-72 | | 20x+60=x^2-8x | | -0.1x-0.45=-0.77 | | -x^2+12x+60=0 | | -10=-x | | 2+12.5v=0.55 | | sqrt(15x^2-12x)=9x | | 4x-2x=5-3 | | sqr(15x^2-12x)=9x | | x-3x=-12 | | (3*x^2+2*y)*dx+(2*x-3)*dy=0 |

Equations solver categories